2002
DOI: 10.1002/tera.90002
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of birth defects to infant mortality in the United States

Abstract: Birth defects remain the leading cause of infant death in the United States, despite the changes that resulted in 1999 from an update in the coding of cause of death from ICD-9 to ICD-10. While birth defects-specific IMRs provide an overall picture of fatal birth defects and a gauge of the impact of life-threatening anomalies, they represent only a fraction of the impact of birth defects, missing those who survive past infancy and those birth defects related losses in the antepartum period. Expansion and suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 2 publications
1
96
0
Order By: Relevance
“…9 In this study most patients admitted with congenital heart defects were infants, followed by toddlers and preschoolers. Only 7.8% children were enrolled who reached puberty and adolescent in >10 years age group.…”
Section: Discussionmentioning
confidence: 72%
“…9 In this study most patients admitted with congenital heart defects were infants, followed by toddlers and preschoolers. Only 7.8% children were enrolled who reached puberty and adolescent in >10 years age group.…”
Section: Discussionmentioning
confidence: 72%
“…10 Major birth defects also continue to be the leading cause of infant mortality in the United States, 11 and costs for care and treatment of children with major birth defects annually totals millions of dollars. 12 Canfield et al 10 used pooled data from 11 states with active case finding to calculate national birth prevalence estimates for 18 selected defects.…”
Section: Substantial Public Health Burdenmentioning
confidence: 99%
“…Accepted for publication Mar 28, 2014 Congenital heart disease (CHD) is one of thecommoncausesofdeathininfancy. [1][2][3][4] Although the outcome has improved over the past decades, morbidity and mortality remain high, especially in infants with critical congenital heart disease (CCHD) in which circulation is dependent on ductal or interatrial shunting. [5][6][7] A large Swedish populationbased study reported that the risk of being discharged with undiagnosed duct-dependent CCHD was 28%.…”
mentioning
confidence: 99%